SISTEM INFORMASI PENGARSIPAN BERBASIS ANIMASI 3D DI LEMBAGA PENDIDIKAN KOMPUTER PRATAMA MULIA SURAKARTA - Sutikno, Arif; Sumirat, Estiarto Wahyu; ., Haryani (Speed - Sentra Penelitian Engineering dan Edukasi, 2009)
Pratama Mulia Surakarta Computer Course complain that the Existed Archieving System they owned not in proportion, closed, undevelopable and become to failure. According to system life cycle principles, the management have to plan for a new one as an expected system. So the problem are : â€œIs it right that the existed system not in proportion, closed, undevelopable and become to failure?, how to design an expected system to replace and eliminate the weakness of the existed one?â€ The goals of this scripts are : The first is â€œProve that the existed system is not in proportion, closed, undevelopable and become to failureâ€, the second is â€œBuild an expected system called 3D Animation Based Archieving System of Pratama Mulia Surakarta to eliminate the weakness of existed systemâ€, the third is â€œCreate a prototype of application for computer system that will be applied as an sub-system of this systemâ€, and the fourth is â€œCreate a system implementation planningâ€. The usage of methodology to solve the problem are â€œObserve with questionairing supported by interviewing, system analysis and designâ€ taken from Kendall and Kendall theory to get the understanding of existed system, â€œfeasibility studyâ€ with feasibility impact grid taken from Kendall and Kendall theory, and â€œImplementation planning theoryâ€ taken from the book writen by Suryadi, H.S. and Bunawan. After the subjects above already done, this script reports that it is true and proved that the existed system is not in proportion (means not all of the goals accomplished by the system), closed, undevelopable and become to failure (means going to or disposed towards failure), an expected system to replace and eliminate the weakness of the existed system itâ€™s already done and ready to implement for Pratama Mulia Surakarta Computer Course.